2019
DOI: 10.2739/kurumemedj.ms664009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Calprotectin Levels in Patients with Inflammatory Bowel Disease

Abstract: Background: Fecal calprotectin has been proposed as a useful biomarker of disease activity in inflammatory bowel disease (IBD). However, the role of calprotectin in systemic circulation is not well established. Thus, this study aimed to quantify serum calprotectin levels to identify a potential inflammatory marker for IBD. Methods: Ninety-eight patients with ulcerative colitis (UC) and 105 patients with Crohn's disease (CD) were prospectively enrolled and clinically scored. Ninety-two healthy, age-matched subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Systemic inflammatory biomarkers, including sCp, were similar in clinically active and inactive UC, consistent with a study reporting similar sCp levels in active and inactive UC. 18 Compared to fCp (AUC 0.85), ROC curve analysis confirmed the poorer diagnostic performance of systemic inflammatory biomarkers in discriminating between active and inactive UC, including both sCp assays (AUC 0.61) and of these sCRP (AUC 0.69) performed best consistent with previous studies. 3,11 In addition, fCp correlated weakly with both sCp assays and sCRP and not at all with platelets.…”
Section: Discussionsupporting
confidence: 85%
“…Systemic inflammatory biomarkers, including sCp, were similar in clinically active and inactive UC, consistent with a study reporting similar sCp levels in active and inactive UC. 18 Compared to fCp (AUC 0.85), ROC curve analysis confirmed the poorer diagnostic performance of systemic inflammatory biomarkers in discriminating between active and inactive UC, including both sCp assays (AUC 0.61) and of these sCRP (AUC 0.69) performed best consistent with previous studies. 3,11 In addition, fCp correlated weakly with both sCp assays and sCRP and not at all with platelets.…”
Section: Discussionsupporting
confidence: 85%
“…62 SC is increased in IBD and distinguishes active from inactive disease in CD, but perhaps not in UC. 35,37,63 Although we found mixed results regarding its predictive ability for disease complications and treatment outcomes, lower levels of SC were generally associated with better future outcomes. 27,[36][37][38] Circulating eNAMPT (visfatin) is predominantly produced and secreted by granulocytes.…”
Section: Discussionmentioning
confidence: 76%
“…Several studies have looked at fecal CALP as a good inflammatory marker for Inflammatory Bowel Disease (IBD). 6,7,15,16 In addition, several researchers discovered a link between fecal CALP and H. pylori infection. 17,18,19 However, no studies have reported the relationship between serum CALP and H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…CALP transduces its inflammatory signaling and plays its role by binding to its receptors on the cell surface, triggering signal transductions via activation of the nuclear factor-κB (NF-kB) transcription factor and Mitogen-Activated Protein 9 Kinases (MAPKs) pathway that induces leukocyte migration and inflammatory cytokine production in inflammatory regions. 6,15 Because serum CALP is a viable blood-based biomarker that is more practical in everyday clinical practice and more acceptable for patients, it has attracted increased interest as a biomarker for IBD. 6 Studies accomplished by Kalla et al 7 and Daniluk et al 21 Colitis (ASUC).…”
Section: Discussionmentioning
confidence: 99%